2016
DOI: 10.16925/od.v12i22.1203
|View full text |Cite
|
Sign up to set email alerts
|

Higiene bucal en la población de San Francisco Antioquia y sus factores relacionados

Abstract: bucal en la población de San Francisco, Colombia, y sus factores relacionados. Rev Nac Odontol. 2016;12(22):23-30. doi: http://dx.doi.org/10. 16925/ od.v12i22.1203 Resumen. Introducción: este artículo describe la higiene bucal de la población de la cabecera municipal de San Francisco, Antioquia (Colombia), según sus condiciones sociodemográficas. Métodos: se realizó un estudio transversal de una muestra no probabilística de la zona urbana del municipio, en personas que se encontraban en las edades trazador… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
2
3
0
7
Order By: Relevance
“…This result is similar to that reported by Ospina et al 8 in a sample of the general population in Colombia. Additionally, Mathur et al 6 found the same tendency among adolescents in a sample of general population in India.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is similar to that reported by Ospina et al 8 in a sample of the general population in Colombia. Additionally, Mathur et al 6 found the same tendency among adolescents in a sample of general population in India.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the scale can be applied to both populations without requiring differential scores. And similarly to what has been reported previously 8,10,11 , the OHHS revealed relatively poor habits: the brushing median corresponded to "frequently", and "never" in the case of flossing.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Recibido: 11 Agosto del 2017 Revisado: 03 Se�embre del 2017 Aceptado: 01 Octubre del 2017 individuo afectando ámbitos importantes como el social y emocional. Entre las patologías que se desencadenan a causa de la placa bacteriana las más frecuentes son la enfermedad periodontal y la caries dental (1)(2)(3)(4)(5) , cada uno postula diferentes superficies dentales a evaluar y distintos parámetros de medición; sin embargo, en epidemiología es necesario utilizar procedimientos simples, claros y rápidos, que otorguen resultados válidos y objetivos para procesarlos estadísticamente.…”
Section: Introductionunclassified